Sorption-Desorption Behavior of Atrazine on Soils Subjected to Different Organic Long-Term Amendments - Lima, D. L. D. (2012)
Sorption of atrazine on soils subjected to three different organic amendments was measured using a batch equilibrium technique. A higher K(F) value (2.20 kg(-1)(mg L(-1))(-)N) was obtained for soil fertilized with compost, which had a higher organic matter (OM) content. A correlation between the K(Foc) values and the percentage of aromatic carbon in OM was observed. The highest K(Foc) value was obtained for the soil with the highest aromatic content. Higher aromatic content results in higher hydrophobicity of OM, and hydrophobic interactions play a key role in binding of atrazine, On the other hand, the soil amended with farmyard manure had a higher content of carboxylic units, which could be responsible for hydrogen bonding between atrazine and OR Dominance of hydrogen bonds compared to hydrophobic interactions can be responsible for the lower desorption capacity observed with the farmyard manure soil, The stronger hydrogen bonding can reduce the leaching of atrazine into drinking water resources and runoff to rivers and other surface waters.